Effect of Metformin Treatment on Insulin Resistance Markers, and Circulating Irisin in Women with Polycystic Ovarian Syndrome (PCOS) - Masaeli, Asiyeh; Nayeri, Hashem; Mirzaee, Mohammadreza (Hormone and Metabolic Research, 2019)
Polycystic ovarian syndrome (PCOS) is considered as a common endocrinal dysfunction among adult women characterized by polycystic ovaries, anovulation, and hyperandrogenism. Irisin is associated with metabolic parameters and insulin resistance. However, the association of irisin with PCOS remains poorly delineated. This study was aimed to examine circulating irisin levels and effects of metformin on this parameter in women with PCOS. Moreover, the association of irisin with insulin resistance markers was determined. Thirty-nine females with PCOS, aged 20–40 years, participated in this study and received 500 mg of metformin once daily for 3 months. Serum creatinine, blood urea nitrogen, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein (LDL), cholesterol, triglyceride, fasting blood sugar, testosterone, 17-hydroxyprogesterone, and irisin were assayed in the studied groups. Circulating irisin was significantly higher in PCOS women. Circulating irisin levels correlated with 17-hydroxyprogesterone, testosterone, and insulin. Three months metformin treatment decreased circulating irisin in PCOS women and improved IR. Circulating irisin is directly associated with insulin resistance in PCOS women and may be used as a biomarker for IR in these patients. Moreover, metformin as a confounding therapy in metabolic diseases can be used to regulate circulating irisin levels in PCOS women.
Keywords: polycystic ovarian syndrome; insulin resistance; irisin